2017
DOI: 10.1016/j.mayocp.2017.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Skilled Nursing Facility Use and Hospitalizations in Heart Failure

Abstract: Objective To examine the impact of skilled nursing facility (SNF) use on hospitalizations among heart failure (HF) patients and to examine predictors of hospitalization among HF patients admitted to a SNF. Patients and Methods Olmsted County, MN residents with first-ever HF from 1/1/2000-12/31/2010 were identified and clinical data were linked to SNF utilization data from CMS. Andersen-Gill models were used to determine the association between SNF use and hospitalizations and to determine predictors of hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
(36 reference statements)
1
6
0
Order By: Relevance
“…In terms of discharge status, our study finds AMI patients were less likely to be discharged to an SNF. This is consistent with prior studies that report no correlation or positive relationship between SNF rates and readmission rates for AMI or heart failure patients (Allen et al, 2011;Chen et al, 2012;Manemann et al, 2017), which challenges perceptions that SNF care will necessarily reduce readmissions. A recent study has also found that deliberate reduction in intensive post-acute care discharges because of incentives created by the Bundled Payment for Care Improvement model is not associated with increase in readmission rates (Jubelt, Goldfeld, Chung, Blecker, & Horwitz, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…In terms of discharge status, our study finds AMI patients were less likely to be discharged to an SNF. This is consistent with prior studies that report no correlation or positive relationship between SNF rates and readmission rates for AMI or heart failure patients (Allen et al, 2011;Chen et al, 2012;Manemann et al, 2017), which challenges perceptions that SNF care will necessarily reduce readmissions. A recent study has also found that deliberate reduction in intensive post-acute care discharges because of incentives created by the Bundled Payment for Care Improvement model is not associated with increase in readmission rates (Jubelt, Goldfeld, Chung, Blecker, & Horwitz, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…Hospitalized patients discharged to SNFs have greater functional dependence than those discharged to home, and therefore, the presence of impaired mobility loses its discriminative value in this high-risk group relative to community-dwelling patients 38 or to those with impaired functional status (or declining status while at a postacute-care rehabilitation facility). 29,33,[39][40][41] This study has several limitations. It was a retrospective study from a single integrated health care delivery system in the upper Midwest with a largely white population.…”
Section: Discussionmentioning
confidence: 96%
“…Although community HF readmission rates average 22%, 30-day HF readmission rates in the SNF setting range from 27% to 43% [ 3 , 5 , 6 ]. There is great interest in reducing this “revolving door” phenomenon within the growing SNF population, as patients are living longer with greater disease severity and multiple comorbidities [ 4 , 7 ]. These readmissions also come at great expense to the health care system, averaging over US $9000 for a typical HF readmission [ 8 ].…”
Section: Introductionmentioning
confidence: 99%